Don't put all your eggs in one basket – Lessons learned from the largest-scale and longest-term wildlife conservation program in the Amazon Basin - Eisemberg, Carla Camilo (Biological Conservation, 2020)
The Brazilian Government established the Amazon Turtle Project (Projeto Quelônios da Amazônia – PQA) in 1975 to monitor and protect the main nesting sites of Amazon River turtles. The PQA has become the largest-scale and longest-term wildlife conservation initiative in the Brazilian Amazon. We evaluated the outcomes of the PQA across 11 protected localities over 30 years (1977–2008). Inside the protected localities, one population of Podocnemis expansa has declined and four have seen an increase in numbers. The PQA conservation efforts for P. unifilis were not as successful as those of Podocnemis expansa, but were sufficient to stabilize or increase populations. These results suggest that there is a minimum effort necessary for positive conservation outcomes, which was not achieved for Podocnemis sextuberculata. Given the lack of correlation between initial nesting numbers and positive population trends, the current level of success in a given locality cannot be used as a tool to prioritize future protection efforts. We recommend that the PQA should maintain or increase its coverage due to the high levels of local unpredictability. If current harvest trends are maintained, it is likely the only surviving populations of P. expansa will be within protected areas. Considering the scope of the PQA and the period that it has been operational, it is surprising how little recognition it has received; the lack of national and international awareness of its achievements may be one of the main reasons behind the lack of support from the Brazilian Government. © 2019 Elsevier Ltd